Risk of Type 2 Diabetes Mellitus following Gestational Diabetes Pregnancy in Women with Polycystic Ovary Syndrome - Joan C. Lo; Jingrong Yang; Erica P. Gunderson; Mohammad K. Hararah; Joel R. Gonzalez; Assiamira Ferrara (Journal of Diabetes Research)
Background. This study examines gestational diabetes mellitus (GDM) in women with polycystic ovary syndrome (PCOS) and the risk of type 2 diabetes mellitus (DM) following GDM pregnancy. Methods. A cohort of 988 pregnant women with PCOS who delivered during 2002–2005 was examined to determine the prevalence and predictors of GDM, with follow-up through 2010 among those with GDM to estimate the risk of DM. Results. Of the 988 pregnant women with PCOS, 192 (19%) developed GDM. Multivariable predictors of GDM included older age, Asian race, prepregnancy obesity, family history of DM, preconception metformin use, and multiple gestation. Among women with PCOS and GDM pregnancy, the incidence of DM was 2.8 (95% confidence interval (CI) 1.9–4.2) per 100 person-years and substantially higher for those who received pharmacologic treatment for GDM (6.6 versus 1.5 per 100 person-years, p<0.01). The multivariable adjusted risk of DM was fourfold higher in women who received pharmacologic treatment for GDM (adjusted hazard ratio 4.1, 95% CI 1.8–9.6). The five-year incidence of DM was 13.1% overall and also higher in the pharmacologic treatment subgroup (27.0% versus 7.1%, p<0.01). Conclusions. The strongest predictors of GDM among women with PCOS included Asian race and prepregnancy obesity. Pharmacologic treatment of GDM is associated with fourfold higher risk of subsequent DM.